Model Komunikasi Interpersonal Generasi Muda Suku Batak Karo di Yogyakarta Melalui Tradisi Ertutur - Bastanta Bernadus Peranginangin; Yudi Perbawaningsih (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2016)
Karonese Batak tribe has ertutur tradition. It is communication of someone when meet people for the first time to get position in the custom and family relationship (pertuturen). When someone meets people for the first time, he or she reduces uncertainty by information seeking. This paper aims at analysing ertutur Karonese tradition as interpersonal communication model for Karonese young people living in Yogyakarta using uncertainty reduction theory. Using qualitative method, data were collected by in-depth interview and participatory observation to Karonese young people living in Yogyakarta. The research found that many young Karonese people living in Yogyakarta have difficulties in starting communication. Ertutur tradition can be one way to start communiation.